Effect of Cognitive Behavioral Intervention Program on Post-Traumatic Stress Disorder Among Syrian Adolescent Refugees in Egypt - Din Fikry, Faten Ezz El-; Abu Nazel, Mervat Wagdy; Sherbini, Hanan Hosni El-; Krit, Amena Abduljbbar (International Journal For Research In Health Sciences And Nursing, 2020)
Abstract: Background: Adolescents' refugee's is directly or indirectly affected by war-related traumas. Many studies had consistently recorded the presence of post-traumatic stress disorder (PTSD) and other psycho-social disorder. However, there is still much discussion about evidence based and sensitive interventions for such problems. Objectives: Assess the prevalence of Post Traumatic Stress Disorder (PTSD) among Syrian adolescents' refugee's students in Egypt and identify the effect of cognitive behavioral intervention program (CBITS) on post-traumatic stress disorder among them. A Quasi experimental research design was adopted to carry out this study. Settings: The study was carried out at 10 schools for Syrian refugees' students at Cairo and Alexandria Governorates. Subjects: All Syrian adolescent refugees' students enrolled in the previously mentioned schools whose age ranged between 11 – 15 years, and was registered in the United Nations High Commissioner for Refugees (UNHCR). Their total number was 613 students in 2014 – 2015 (Appendix 1). b- All students with moderate level of PTSD (206) according to the initial assessment using child PTSD symptom scale (CPSS) were selected to be included in the (CBITS) program. Tools: Two tools were used in this study. Tool I: Students' Personal and Socio- demographic Data Structured Interview Questionnaire. Tool Two: Child PTSD Symptom Scale (CPSS) to assess the frequency of all post-traumatic stress disorder symptoms within the past month among adolescents experienced a traumatic event. The study had four phases. The first was the assessment and preparatory phase were tool (II) used to assess PTSD symptoms frequency and severity among adolescent6s' refugees, the second was the development phase while the third was the implantation phase and Finally the fourth phase was the evaluation phase during which tool (II) was reused for immediate and 3 month follow up evaluation for. Results: Findings of the present study revealed that more than one third (34.75%) of the Syrian adolescent's refugees had mild symptoms of PTSD, one third of them (33.6 %) had moderate symptoms and 4.08% had severe PTSD symptoms. statistically significant difference on PTSD severity either immediately or after three month following the intervention implementing between study and control groups (X2=16.455, P=0.001 and X2=23.486, P=0.01).Conclusion. post-traumatic stress disorder symptoms is prevalent among Syrian adolescent refugees in Egypt. Furthermore, the current study concluded that the cognitive behavioral interventions for trauma in school was promising intervention for reduce of PTSD symptoms among Syrian adolescent refugees' in Egypt. Recommendations: Conduct comprehensive physical and mental health screen and assessment for traumatic adolescent's refugees for PTSD to identify intervention requirements and training for health specialists' practitioners to deliver evidence-based PTSD related interventions